2015
DOI: 10.1103/physreve.91.012112
|View full text |Cite
|
Sign up to set email alerts
|

Frenkel line and solubility maximum in supercritical fluids

Abstract: A new dynamic line, the Frenkel line, has recently been proposed to separate the supercritical state into rigid-liquid and non-rigid gas-like fluid. The location of Frenkel line on the phase diagram is unknown for real fluids. Here, we map the Frenkel line for three important systems: CO2, H2O and CH4. This provides an important demarcation on the phase diagram of these systems, the demarcation that separates two distinct physical states with liquid-like and gas-like properties. We find that the Frenkel line c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 26 publications
1
73
2
Order By: Relevance
“…We observe that all the data points collected in the supercritical region are located on the right side of the Frenkel line reported in Ref. [17] [line (5) in Fig. 1] and thus correspond to liquidlike states.…”
Section: A Experimentsmentioning
confidence: 65%
See 2 more Smart Citations
“…We observe that all the data points collected in the supercritical region are located on the right side of the Frenkel line reported in Ref. [17] [line (5) in Fig. 1] and thus correspond to liquidlike states.…”
Section: A Experimentsmentioning
confidence: 65%
“…Notably, the phase diagram of CO 2 at conditions of high pressure and temperature has been the subject of many investigations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], the main results of which are summarized in Fig. 1.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the points of the minima of the speed of sound in our analysis terminate at 0.5 GPa, approxi mately up to the pressure where the experimental data [8] are available. Above 0.5 GPa and up to 50 GPa, the Frenkel line was located not on the basis of the minima of the speed of sound but using (a) the scaling argument of parallelism between the melting line and the Frenkel line, the parallelism confirmed by recent molecular-dynamics (MD) simulations in several supercritical fluids [9,10], and (b) our previous result from MD simulations that the Frenkel line starts not far from the critical point (around 0.87]-) [3,5,9,10]. This pressure range constitutes almost the entire range of the Frenkel line presented in our Ref.…”
mentioning
confidence: 90%
“…These regions differ by the microscopic dynamics of particles and are separated by a crossover line called Frenkel line. Later on the phenomenon of dynamical crossover was studied for a number of other fluids [4][5][6][7][8].Another topic attracting wide attention of researchers is related to anomalous behavior of liquids (see, for example, [9] for the list of anomalies of water). It was found that models with isotropic pair core-softened potentials can demonstrate anomalous behavior [10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%